Traditional and Cyber-Victimization Among Adolescents With and Without Chronic Pain - Fales, Jessica L. (Health Psychol, 2017)
OBJECTIVE: Prior research has revealed a link between peer victimization and somatic complaints in healthy youth; however, the peer victimization experiences of youth with clinically significant chronic pain have not been examined. This study aims to determine rates of peer victimization among youth seeking treatment for chronic pain and to compare these rates to a community control group. Relationships between peer victimization, depressive symptoms, and functional disability are also examined. METHOD: One hundred forty-three adolescents (70 with chronic pain) completed measures assessing their experience of traditional (physical, relational, reputational) and cyber-based peer victimization, as well as measures assessing their depressive symptoms and pain-related functional disability. RESULTS: Peer victimization experiences were common among youth with and without chronic pain. Within the chronic pain group, there were differences in rates of peer victimization as a function of the adolescent’s school setting. Adolescents with chronic pain attending traditional schools reported more frequent peer victimization experiences than adolescents with pain not enrolled in school or attending online/home school. Within the chronic pain sample, peer victimization was moderately associated with depressive symptoms and functional disability. Tests of a simple mediation model revealed a significant indirect effect of peer victimization on functional disability, through depression. CONCLUSIONS: These results are the first to systematically document the peer victimization experiences of adolescents with chronic pain. Peer victimization is commonly experienced, particularly for those enrolled in traditional school settings. Associations with depressive symptoms and functional disability suggest that peer victimization may be a useful target for intervention.